2009
DOI: 10.1159/000257517
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase-derived ROS Contributes to Upregulation of TRPC6 Expression in Puromycin Aminonucleoside-induced Podocyte Injury

Abstract: Recent studies have demonstrated upregulation of transient receptor potential cation channel 6 (TRPC6) contributes to podocyte injury in acquired forms of proteinuric kidney diseases, such as focal segmental glomerulosclerosis (FSGS). However, under these pathophysiological conditions, the mechanisms of regulation of TRPC6 expression and activity remain unknown. The present study tested the hypothesis that NADPH oxidase-mediated redox signaling importantly participates in the development of podocyte injury by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 39 publications
6
69
0
1
Order By: Relevance
“…Furthermore, these results do not preclude a role for Nox5 in other forms of nephropathy, such as FSGS, in which ROS production has been implicated. 14 Given that enhanced Nox5 activity in podocytes is sufficient to induce filtration barrier dysfunction, it is possible that additional investigation may uncover a role for Nox5 in other forms of CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these results do not preclude a role for Nox5 in other forms of nephropathy, such as FSGS, in which ROS production has been implicated. 14 Given that enhanced Nox5 activity in podocytes is sufficient to induce filtration barrier dysfunction, it is possible that additional investigation may uncover a role for Nox5 in other forms of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models of minimal change disease, membranous nephropathy, and FSGS, inhibition of Nox activity is associated with decreased podocyte effacement and amelioration of albuminuria. [11][12][13][14] In models of diabetic nephropathy, treatment with the Nox inhibitor apocynin, as well the antioxidant vitamin E, reduces oxidative stress, podocyte effacement and loss, and albuminuria. 6,15,16 Noxs are regulated by many factors, including the renin angiotensin aldosterone system.…”
mentioning
confidence: 99%
“…Recent studies have demonstrated that TRPC6 also represents a target of ROS in different disease models (98,443,446). Using lung ischemia-reperfusion edema (LIRE) model, Weissmann et al (446) elegantly showed that NOX2-mediated O 2 -activates TRPC6 and thereby induces Ca 2 + influx in endothelial cells.…”
Section: A Altered Intracellular Ca 2 + Regulationmentioning
confidence: 99%
“…The roles of Nox4 in the effacement and apoptosis of podocytes have been studied in an experimental diabetic mice model and in a puromycin aminonucleoside-induced rat model of focal segmental glomerulosclerosis (32,(45)(46)(47). We also have reported, in a previous publication, that inhibition of Nox4 by the pharmacological inhibitor diphenyleneiodonium or RNA interference ameliorates TGF-␤1-mediated oxidative stress, mitochondrial dysfunction, and apoptosis in podocytes (31).…”
Section: Volume 290 • Number 52 • December 25 2015mentioning
confidence: 99%